Uprooted : the Japanese American experience during World War II - Marrin, Albert (Alfred A. Knopf, 2016)
Highlights the struggles of Japanese Americans during World War II when the U.S. government placed more than 100,000 of its own citizens in concentration camps. Includes resources for further information maps, and photographs.